Motivasi dan Disiplin Kerja: Kunci Kinerja Optimal Karyawan PT Yudhistira Ghalia Indonesia Parepare - Adrian, Adrian; D'Ornay, Anastasia; Alimuddin, Firman; Anggerwati, A. Indah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This research aims to determine work motivation and work discipline at the company PT. Yudhistira Ghalia Indonesia Parepare Branch. The analysis method used is descriptive quantitative, using primary data sourced from the results of questionnaires that have been answered by respondents. The tests used include validity test, reliability test, descriptive analysis, multiple linear regression analysis and t test (partial), f test (simultaneous), R2 test (coefficient of determination). The results of this research show that work motivation has a partial effect on employee performance with a calculated t value of 4,834 > 2,034 with a significant level of 0.000 > 0.05, company work discipline has a partial effect on employee performance with a calculated t value of 7,068 > 2,034 with a significant level of 0.000 < 0.05. Work Motivation and Work Discipline simultaneously influence employee performance with a calculated F value of 177.203 > 3.28 with a significance level of 0.000 < 0.05.